2015
DOI: 10.1051/0004-6361/201526377
|View full text |Cite
|
Sign up to set email alerts
|

First detection of the 63μm atomic oxygen line in the thermosphere of Mars with GREAT/SOFIA

Abstract: Context. The Stratospheric Observatory for Infrared Astronomy (SOFIA) with its 2.5 m telescope provides new science opportunities for spectroscopic observations of planetary atmospheres in the far-infrared wavelength range. Aims. This paper presents first results from the 14 May, 2014 observing campaign of the Martian atmosphere at 4.7 THz using the German REceiver for Astronomy at Terahertz frequencies (GREAT) instrument. Methods. The atomic oxygen 63 µm transition, OI, was detected in absorption against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The other was derived from Mars Climate Database (MCD) [ González‐Galindo et al , ], represents larger concentrations of oxygen, and results in stronger cooling by CO 2 . Recent globally averaged measurements [ Rezac et al , ; Mahaffy et al , ] hint that oxygen density profiles lie somewhere between the Nair and MCD models. We denote these scenarios in our discussions as N94 and MCD, correspondingly.…”
Section: Co2 Densitymentioning
confidence: 99%
“…The other was derived from Mars Climate Database (MCD) [ González‐Galindo et al , ], represents larger concentrations of oxygen, and results in stronger cooling by CO 2 . Recent globally averaged measurements [ Rezac et al , ; Mahaffy et al , ] hint that oxygen density profiles lie somewhere between the Nair and MCD models. We denote these scenarios in our discussions as N94 and MCD, correspondingly.…”
Section: Co2 Densitymentioning
confidence: 99%
“…The 63.184 μm emission has been observed from balloons [Naylor et al, 1985;Lin et al, 1987;Mlynczak et al, 2004], rocket [Feldman and McNutt, 1969;Offermann and Grossmann, 1978], and space shuttles [Grossmann et al, 2000]. New airborne instruments for astronomy, such as Far Infrared Field-Imaging Line Spectrometer [Klein et al, 2010] and German REceiver for Astronomy at Terahertz frequencies (GREAT) [Rezac et al, 2015], have also observed the terrestrial OI emissions in surveying astronomical objects.…”
Section: 1002/2015ja022314mentioning
confidence: 99%
“…10 Since the first flight, many discoveries have been enabled with this LO, for example, the first detection of the OI line in the atmosphere of Mars. 100 In Fig. 12, seven OI spectra of W49 N, a star-forming region about 36 200 light years away from Earth, are shown.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%